Forest lookout tower visitor data in the Covid epidemic periods: what the numbers tell - Czibula, György (Acta Agraria Debreceniensis, 2024)
The Covid epidemic between the spring of 2020 and the summer of 2021 showed that there is an increasing demand for various forms of forest-related tourism. Number of visitors in forests broke records in certain places: 32 million visitor days were registered in 2020 in Pilisi Parkerdő Ltd. alone. In this article we present data originated from the automatic visitor counters placed on certain forest lookout towers. Processing the data, we can get an insight of the number and distribution of hikers in each period. As a result of the research, forest managers can learn more about the popular tourist destination, furthermore, knowledge is gained about the motivations and needs of forest tourism participants. Based on this, public welfare investments that meet real demands can be planned in a cost-effective manner. Ideally, the results achieved can bring satisfaction to all actors involved in forest tourism. On the demand (visitor) side, targeted and needs-tailored developments increase the experience factor of the time spent in the forest. On the supply (forestry) side, knowing the motivations makes the performance of public welfare tasks more efficient, which ultimately contributes to the improvement of the sector’s image.